The development of a self-management intervention for stroke survivors – My Life After Stroke (MLAS). Issue 2 (16th January 2023) - Johnson, Vicki L.; Apps, Lindsay; Hadjiconstantinou, Michelle; Carey, Marian E.; Kreit, Elizabeth; Mullis, Ricky; Mant, Jonathan; Davies, Melanie J.
Abstract: Purpose: Long-term needs of stroke survivors (especially psychosocial needs and stroke prevention) are not adequately addressed. Self-management programmes exist but the optimal content and delivery approach is unclear. We aim to describe the process undertook to develop a structured self-management programme to address these unmet needs. Materials and methods: Based on the Medical Research Council framework for complex interventions, the development involved three phases: "Exploring the idea": Evidence synthesis and patient and public involvement (PPI) with stroke survivors, carers and healthcare professionals. "The iterative phase": Development and iterative refinement of the format, content, underpinning theories and philosophy of the self-management programme My Life After Stroke (MLAS), with PPI. MLAS consists of two individual appointments and four group sessions over nine weeks, delivered interactively by two trained facilitators. It aims to build independence, confidence and hope and focusses on stroke prevention, maximising physical potential, social support and managing emotional responses. MLAS is grounded in the narrative approach and social learning theory. "Ready for research": The refinement of a facilitator curriculum and participant resources to support programme delivery. Results: Through a systematic process, we developed an evidence- and theory-based self-management programme for stroke survivors Conclusions: MLAS warrants evaluation in a feasibility study. Implications for rehabilitation: My Life After Stroke(MLAS) has been developed using a systematic process, to address the unmet needs of stroke survivors. This systematic process, involved utilising evidence, theories, patient and public involvement, expertise and guidelines from other long-term conditions. This may further help the development of similar self-management programme within the field of stroke. MLAS warrants further evaluation within a feasibility study.